2020
DOI: 10.3390/cancers12123660
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Cystatin F Is Internalised by Cytotoxic T Lymphocytes and Decreases Their Cytotoxicity

Abstract: Cystatin F is a protein inhibitor of cysteine cathepsins, peptidases involved in the activation of the effector molecules of the perforin/granzyme pathway. Cystatin F was previously shown to regulate natural killer cell cytotoxicity. Here, we show that extracellular cystatin F has a role in regulating the killing efficiency of cytotoxic T lymphocytes (CTLs). Extracellular cystatin F was internalised into TALL-104 cells, a cytotoxic T cell line, and decreased their cathepsin C and H activity. Correspondingly, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Cystatin F is only partially targeted to endo-lysosomes upon its synthesis, and can also be secreted and taken up by surrounding cells (188). The uptake of exogenous cystatin F was also shown to reduce the cytotoxicity of NK cells and T cells (188,216). Furthermore, proinflammatory cytokines, such as IFN-g and TNF-a, increase cathepsin S and B activities in DCs (217,218), whereas IL-10, which induces tolerogenic DCs and consequently T lymphocyte anergy (219), prevents the upregulation of cathepsin S and B activities in DCs (220).…”
Section: The Role Of Cathepsins and Their Inhibitors In Inducing Tolerance And Anergy In Immune Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cystatin F is only partially targeted to endo-lysosomes upon its synthesis, and can also be secreted and taken up by surrounding cells (188). The uptake of exogenous cystatin F was also shown to reduce the cytotoxicity of NK cells and T cells (188,216). Furthermore, proinflammatory cytokines, such as IFN-g and TNF-a, increase cathepsin S and B activities in DCs (217,218), whereas IL-10, which induces tolerogenic DCs and consequently T lymphocyte anergy (219), prevents the upregulation of cathepsin S and B activities in DCs (220).…”
Section: The Role Of Cathepsins and Their Inhibitors In Inducing Tolerance And Anergy In Immune Cellsmentioning
confidence: 99%
“…Silencing of naturally occurring cathepsin inhibitors, such as cystatins and serpins, which attenuate the cytosolic activity of cathepsins and hence LMP-driven apoptosis, may induce apoptosis and consequently be therapeutically useful in autoimmune lymphocyte populations, pathogen-infected cells, and tumor cells. In addition, recent findings (188,216) suggest that decreasing the intracellular uptake or activation of cystatin F could increase the efficacy of target cell killing by cytotoxic cells (NK cells and CD8+ T cells), thus improving the antitumor immune response.…”
Section: M2mentioning
confidence: 99%
“…This raises the possibility that CF‐producing cells can regulate the endo‐lysosomal cysteine protease activities of non‐producing neighbours. Indeed uptake of CF into human CTL resulted in the suppression of multiple cathepsin activities, reduced granzyme activity and reduced killing ability [ 136 ]. Since some tumour cells express cystatin F [ 137 ], this might have been adopted as a strategy to evade a CTL response.…”
Section: Innate and Adaptive Immunity: Lysosome‐related Organelles In...mentioning
confidence: 99%
“…Finally, CysF was found to be expressed in patient‐derived glioblastoma stem‐like cells [ 211 ]. Recently, it was shown that extracellular CysF attenuates granzyme‐mediated cytotoxicity in CTLs [ 213 ] and decreases the susceptibility of a glioblastoma cell line to NK cytotoxicity [ 211 ]. Apart from the effects on properforin and granzyme activation, increased extracellular CysF levels can affect the activity of immune cells through several additional mechanisms.…”
Section: Lysosomal Peptidases In Cancer Progressionmentioning
confidence: 99%